Implementasi Sistem Pengendalian Internal Pemerintah dalam Pengelolaan Keuangan Pemilu di Bawaslu Provinsi Banten - Nabil Zahran Aryadi; Nadia Khumairatun Nisa, S.Sos., M.I.P; Sandy Amllatied Imanisakti; Zaldi Hafidz Fachrureta; Muhammad Catur Fauzan; Rifan Maulana (HK Publishing, 2026)
This study aims to analyze the implementation of the Government Internal Control System (SPIP) based on the COSO framework in mitigating the risk of election financial management deviations at the Election Supervisory Body (Bawaslu) of Banten Province, as well as to identify its structural and managerial barriers. The study employed a qualitative approach with a single instrumental case study design. Empirical data collection was conducted through purposive in-depth interviews with the Head of the Administration Division and financial management staff, supported by operational observations in the field. Data validity was tested through source and method triangulation, while data analysis applied the Miles and Huberman interactive model. The results show that all five COSO components have been implemented, ranging from Command Center supervision to digital document audits. However, the effectiveness of these instruments has not achieved a zero-fraud governance ecosystem due to the high penetration of bureaucratic barriers. Structurally, governance is hampered by a human resource regeneration crisis because regulations mandate Civil Servant (PNS) status for treasury positions, triggering overlapping duties, workload asymmetry, and exacerbated by technological infrastructure limitations (blank spots) in regional areas. Managerially, supervisory effectiveness is paralyzed by the time compression phenomenon between the execution of election stages and accounting reporting deadlines. This massive operational workload ultimately triggers document backlogs and generates an erosion of administrative compliance culture among supervisory apparatus. Keywords: Bawaslu; COSO; Bureaucratic Barriers; Election Financial Management; Internal Control System